L-Band Receiver Design For Scatterometer - Chua, Ming Yam (2007)
In this work, a Radio Frequency (RF) receiver system is constructed for an L-band Scatterometer system. The receiver is designed to operate at 1.4GHz frequency (21 cm wavelength) by using frequency-modulated continuous wave (FMCW) technique.